2017
DOI: 10.1190/tle36121025.1
|View full text |Cite|
|
Sign up to set email alerts
|

Seismic monitoring leveraging existing telecom infrastructure at the SDASA: Active, passive, and ambient-noise analysis

Abstract: We analyze active and passive seismic data recorded by the Stanford distributed acoustic sensing array (SDASA) located in conduits under the Stanford University campus. For the active data we used low-energy sources (betsy gun and sledge hammer) and recorded data using both the DAS array and 98 three-component nodes deployed along a 2D line. The joint analysis of shot profiles extracted from the two data sets shows that some surface waves and refracted events are consistently recorded by the DAS array. In area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…The Stanford DAS array recorded and stored continuous data from 620 independent seismic channels at a frequency of 50 samples per second with 7.14 m gauge length and 8.16 m channel spacing. Through this experiment Martin et al () showed that DAS technology can be used to record seismic data directly from a free‐floating cable in a horizontal PVC conduit. Furthermore, by analyzing adjacent earthquakes on nearby faults, Biondi et al () demonstrated that signals recorded using this cable provide repeatable and reliable ground motion measurements.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Stanford DAS array recorded and stored continuous data from 620 independent seismic channels at a frequency of 50 samples per second with 7.14 m gauge length and 8.16 m channel spacing. Through this experiment Martin et al () showed that DAS technology can be used to record seismic data directly from a free‐floating cable in a horizontal PVC conduit. Furthermore, by analyzing adjacent earthquakes on nearby faults, Biondi et al () demonstrated that signals recorded using this cable provide repeatable and reliable ground motion measurements.…”
Section: Methodsmentioning
confidence: 99%
“…We apply passive Rayleigh wave interferometry to the DAS channels along Via Ortega using 1 year of continuous data starting from early September 2016 (Martin et al, ). Only a collinear sub‐array is used for interferometry because that virtual‐source configuration is expected to yield Rayleigh waves (Martin et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since September 2016, the Stanford Fiber Optic Seismic Observatory has been continuously collecting passive seismic data at a rate of 50 samples per second at 4 meter channel spacing on 2.5 km of fiber optic cables in existing telecommunications conduits underneath the Stanford University campus (Martin et al, 2018). It is the longest running, ultra-dense urban seismic experiment, and has been used to ambient noise interferometry, earthquake detection (Lindsey et al, 2017), and active seismic acquisition (Martin et al, 2017). An array with similar settings that covered 1000 km (a reasonable length for an array covering a major metropolitan area in an earthquake-prone region) would collect 0.5 petabytes of data annually, so some form of lossy compression will need to be part of any scalable plan for future DAS data archiving.…”
Section: Application To Passive Das Datamentioning
confidence: 99%